Integrative physiological and transcriptome analysis unravels the mechanism of low nitrogen use efficiency in burley tobacco - Yuqing Feng; Yuanyuan Zhao; Yanjun Ma; Xiaolong Chen; Hongzhi Shi (Plant Direct)
Abstract Burley tobacco, a chlorophyll‐deficient mutant with impaired nitrogen use efficiency (NUE), generally requires three to five times more nitrogen fertilization than flue‐cured tobacco to achieve a comparable yield, which generates serious environmental pollution and negatively affects human health. Therefore, exploring the mechanisms underlying NUE is an effective measure to reduce environmental pollution and an essential direction for burley tobacco plant improvement. Physiological and genetic factors affecting tobacco NUE were identified using two tobacco genotypes with contrasting NUE in hydroponic experiments. Nitrogen use inefficient genotype (TN90) had lower nitrogen uptake and transport efficiencies, reduced leaf and root biomass, lower nitrogen assimilation and photosynthesis capacity, and lower nitrogen remobilization ability than the nitrogen use efficient genotype (K326). Transcriptomic analysis revealed that genes associated with photosynthesis, carbon fixation, and nitrogen metabolism are implicated in NUE. Three nitrate transporter genes in the leaves (NPF2.11, NPF2.13, and NPF3.1) and three nitrate transporter genes (NPF6.3, NRT2.1, and NRT2.4) in roots were down‐regulated by nitrogen starvation, all of which showed lower expression in TN90 than in K326. In addition, the protein–protein interaction (PPI) network diagram identified eight key genes (TPIP1, GAPB, HEMB, PGK3, PSBO, PSBP2, PSAG, and GLN2) that may affect NUE. Less advantageous changes in nitrogen uptake, nitrogen assimilation in combination with nitrogen remobilization, and maintenance of photosynthesis in response to nitrogen deficiency led to a lower NUE in TN90. The key genes (TPIP1, GAPB, PGK3, PSBO, PSBP2, PSAG, and GLN2) were associated with improving photosynthesis and nitrogen metabolism in tobacco plants grown under N‐deficient conditions.